Bandwidth control of loop type frequency selective surfaces using dual elements in various arrangements. (17th November 2021) - Littman, Nickolas; O'Keefe, Steven G; Galehdar, Amir; Espinosa, Hugo G; Thiel, David V
Abstract: Frequency selective surfaces (FSSs) have applications across multiple disciplines due to their unique electromagnetic properties. This paper investigates the use of both rounded square loops, and simple loop type dual elements arranged in unique patterns, to control the transmission and reflection bandwidth and resonant frequencies over KU and K frequency bands supported by equivalent circuit models. The FSSs were fabricated using laser engraving to create conductive loop type elements on a thin, flexible and optically transparent Mylar substrate (relative permittivity of 2.7 and thickness of 65 μ m). The frequency response of the surfaces are controlled through the element self-inductance and capacitive coupling with neighbouring elements. This work shows that different arrangements result in the formation of multiple distinct resonances. The theoretical and experimental results were in good agreement where rounded squares and dual element arrays were employed to create broadband and multiband band-stop FSSs. A polarization sensitive surface exhibited stop-bands at 12 and 16 GHz in transverse electric polarization and a stop-band at 14.4 GHz in transverse magnetic polarization. This technique can be applied to any periodic array through careful selection of the individual elements in the array, as well as their arrangement.